The Effect of Anticipated and Unanticipated Inflation on Income Distribution: The Israeli Case - Silber, J.; Zilderfarb, B.Z. (Journal of Income Distribution®, 1995)
This paper examines the distributional effects of inflation and unemployment in Israel. Unlike previous studies, it distinguishes between the effect of expected and unexpected inflation, arguing that the latter should have a stronger effect. The empirical results show that a deterioration in macroeconomic conditions (a rise in inflation and/or unemployment) reduces the income share of the lower half of Israeli households and increases the income share of the wealthiest 20 per cent. The effect of unanticipated inflation is found, indeed, to be 67 per cent stronger than that of expected inflation.